Increasing Efficiency and Quality by Consolidation of Clinical Chemistry and Immunochemistry Systems with MODULAR ANALYTICS SWA. (21st January 2008) - Mocarelli, Paolo; Horowitz, Gary L.; Gerthoux, Pier Mario; Cecere, Rossana; Imdahl, Roland; Ruinemans-Koerts, Janneke; Luthe, Hilmar; Calatayud, Silvia Pesudo; Salve, Marie Luisa; Kunst, Albert; McGovern, Margaret; Ng, Katherine; et al.
Abstract : MODULAR ANALYTICS Serum Work Area (in USA Integrated MODULAR ANALYTICS, MODULAR ANALYTICS is a trademark of a member of the Roche Group) represents a further approach to automation in the laboratory medicine. This instrument combines previously introduced modular systems for the clinical chemistry and immunochemistry laboratory and allows customised combinations for various laboratory workloads. Functionality, practicability, and workflow behaviour of MODULAR ANALYTICS Serum Work Area were evaluated in an international multicenter study at six laboratories. Across all experiments, 236000 results from 32400 samples were generated using 93 methods. Simulated routine testing which included provocation incidents and anomalous situations demonstrated good performance and full functionality. Heterogeneous immunoassays, performed on the E-module with the electrochemiluminescence technology, showed reproducibility at the same level of the general chemistry tests, which was well within the clinical demands. Sample carryover cannot occur due to intelligent sample processing. Workflow experiments for the various module combinations, with menus of about 50 assays, yielded mean sample processing times of< 38 minutes for combined clinical chemistry and immunochemistry requests;< 50 minutes including automatically repeated samples. MODULAR ANALYTICS Serum Work Area offered simplified workflow by combining various laboratory segments. It increased efficiency while maintaining or even improving quality of laboratory processes.